2022
DOI: 10.3389/fmicb.2022.787739
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Assembly of a Porcine Epidemic Diarrhea Virus Infectious cDNA Clone by Homologous Recombination in Yeast: Rapid Manipulation of Viral Genome With CRISPR/Cas9 Gene-Editing Technology

Abstract: Porcine epidemic diarrhea virus (PEDV), a swine enteric coronavirus causing acute diarrhea in piglets, is one of the major threatens to the pork industry globally. Reverse genetics is a valuable tool for the virological study and vaccine development for coronaviruses. Due to the large size and unstable problem in Escherichia coli of coronavirus genome, construction and manipulation of reverse genetics system for coronaviruses remain laborious and time-consuming. In this study, a reverse genetics system of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Then, the cell lines were exposed to a reporter virus (rPEDV-EGFP) engineered to express enhanced GFP (EGFP) during replication. This reporter virus replicated well in Vero CCL-81 cells [16]. We repeatedly detected some EGFP expression in HepG2, Hep3B217, and SNU387 cells as well as the Huh7 cells, whereas there was no GFP expressed in Li7, SNU182, and SNU761 cells (Figure 1C).…”
Section: Selection Of Cell Lines For Pedv Infectionmentioning
confidence: 73%
See 1 more Smart Citation
“…Then, the cell lines were exposed to a reporter virus (rPEDV-EGFP) engineered to express enhanced GFP (EGFP) during replication. This reporter virus replicated well in Vero CCL-81 cells [16]. We repeatedly detected some EGFP expression in HepG2, Hep3B217, and SNU387 cells as well as the Huh7 cells, whereas there was no GFP expressed in Li7, SNU182, and SNU761 cells (Figure 1C).…”
Section: Selection Of Cell Lines For Pedv Infectionmentioning
confidence: 73%
“…The PEDV-SD strain was isolated and stored in our laboratory. Recombinant rPEDV-EGFP was produced by transfecting infectious cDNA clones into BHK21 cells as previously described [16]. The viruses were titrated on the Vero CCL-81 cells by TCID 50 .…”
Section: Cells Viruses and Antibodiesmentioning
confidence: 99%
“…Rapid assembly of the whole CoV genome in one time is the main advantage for yeast-based method. However, this method needs extract yeast plasmid from yeast culture; yeast plasmid extraction is more complicated, time-consuming, and expensive than bacterial plasmid extraction [42].…”
Section: Yeast-based Methodsmentioning
confidence: 99%
“…An advantage of using the yeast system for constructing a CoV reverse genetics system is that > 10 cDNA fragments can be ligated simultaneously such that the total fragment length exceeds 110 kb. In 2022, Zhou et al reported the construction of a PEDV reverse genetics system using the yeast system [42]. The sequences of CMV promoter, HDVr, and BGH termination signal sequence were cloned into pYES1L vector to obtain the vector pYES1L-CMV-HDVrbz-BGH.…”
Section: Yeast-based Methodsmentioning
confidence: 99%
“…The gaussia luciferase assay was performed with coelenterazine h substrate (Maokang Biochem, Shanghai, China) as described previously ( Zhou et al., 2022 ). The substrate was prepared by diluting coelenterazine h stock to 20 μM with PBS supplemented with 5 mM NaCl, pH 7.2, and incubated at RT in the dark for 30 min.…”
Section: Methodsmentioning
confidence: 99%